Association Between use of Interdental Cleansing Aids Gingival Conditions in Fixed Dental Prosthesis Patients - Basnyat, S. K.C.; Sapkota, B.; Shrestha, S.; Rimal, U. (Kathmandu University Medical Journal, 2020)
Background The fixed dental prosthesis are one of the most commonly used prosthesis which are difficult for cleansing in dental clinical practice especially the interproximal areas. As a result, periodontal disease most commonly develops in interproximal areas. The efficacy of using dental floss and interdental brushing in addition to tooth brushing reduce plaque and gingival inflammation. Objective To assess gingival condition in patients after placement of fixed dental prosthesis for a period of 3 months who regularly use or do not use dental floss and interdental brushing. Method Patients visiting the Dental Outpatient Department of Dhulikhel Hospital were selected for study. The examination was conducted using basic diagnostic tools (Mouth mirror, periodontal probe and explorer). The total number of patients involved in the study were 200. Teeth and gingiva were examined using the Plaque (Silness and Loe) and Gingiva Index (Löe and Silness). The examinations were conducted after 15 days and 3 months of placement of fixed dental prosthesis along with the oral hygiene instructions. Chi-square test and McNemar Bowker test were done to find statistical association using SPSS 20.0. Result Statistical analysis showed that there was association between frequency of interdental cleaning and plaque index (p=0.012) and gingival index (p=0.036) examined in 15 days and 3 months. Conclusion Use of Interdental cleansing aids was statistically significant to oral hygiene outcomes i.e. plaque index and gingival index. Oral hygiene instructions play a vital role in improving overall oral health.